Trajetórias sociais e educacionais de mulheres vítimas de violência - Schneider, Cristiane (2022)
This dissertation presents the reconstruction of the social and educational trajectories of women victims of violence, who participate in the Borboleta Project, belonging to the Court of Justice of the city of Porto Alegre, questioning dimensions and manifestations of the female habitus built during their lives. The family education is part of the trajectory of these women, who have occupied different positions throughout their lives. As a justification for carrying out this research, in addition to carrying out a theoretical reflection on this topic that requires an even more effective look at the public spheres, it is necessary for the academy to also position itself, seeking movements and knowledge that reverberate in the reduction of high indices of violence, as well as the role of education when it comes to gender violence against women. The study was carried out from Pierre Bourdieu's Constructivist Structuralism, having as main concepts of this theory: the social trajectory and the female habitus, complemented by theoretical counterpoints elaborated by Bernard Lahire and Michael Apple in extensions and discussions of this theory, especially when in this research the study of schooling in these trajectories is addressed. The concepts of critical route and against pedagogies of cruelty were also addressed, researched by Latin American feminists Montserrat Sagot and Rita Segato, who deal with issues related to violence against women. The research showed that educational spaces constitute relevant areas in these trajectories, with formal and non formal education being an important path for women who travel the critical route, but that issues related to efficient public policies, prepared to carry out effective work and that really fulfill the purpose of helping these women, is still very deficient.